Distopia Na Cultura De Massa: Netflix E A Série 3% - Santos, Amanda Ferreira [UNIFESP] (2018)
The Year Is 2011. In Youtube, A Pilot Episode Appears, For A Brazilian Series With An Innovative Theme: In A Future And Dualized Brazil, Young People From The Less Fortunate Side, When They Turn 20 Years Old, They Have A One And Only Chance To Gain A Place In The Favored Society Of The Offshore, Where They"Ll Have Access To Technology And Comfort For The Rest Of Their Lives. However, Only 3 Percent Of The Candidates Succeed. With A Dystopian But Contemporary Theme, It Was Highlighted By Being The First All-Brazilian Production By Netflix, Conquering Fans From Around The Globe As Well. This Dissertation, Divided In Two Parts, Tries To Determine The Elements That Compose The Series, From The Importance Of The Streaming Services To The Change In The Relationship Between Spectator And Tv, Through The Establishment Of Netflix In Brazil And, Consequently, The Decision To Make 3% A Part Of Its Worldwide Catalog, To Study Its Narrative Elements, Its Cinematography And, Of Course, To Make A Comparison With The 2011"S